FOREIGN LANGUAGE ANXIETY AMONG ISLAMIC DEGREE STUDENTS: EXPLORING ITS IMPACT ON ACADEMIC PERFORMANCE AT THE TERTIARY LEVEL INSTITUTION - Noormaizatul Akmar Muhamad Nasir; Nurul Husna Yaacob; Norma Yaakub; Che Syazana Che Ab Razak, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explores the prevalence and impact of foreign language anxiety (FLA) among Islamic degree students at a tertiary level institution in their English language learning journey. FLA is commonly characterized by uneasiness associated with learning a new or additional language and has been recognized as a psychological barrier in language learning. The study's primary objectives are to identify FLA levels among Islamic degree students and study the correlation between FLA and students' exam grades using the Foreign Language Classroom Anxiety Scale (FLCAS). Employing a quantitative approach, the study administered FLCAS questionnaires to 181 participants, and data analysis was conducted using SPSS. Results revealed that communication apprehension recorded the highest mean (3.43), signifying a high degree of anxiety among the respondents. Conversely, the remaining FLCAS components, namely test anxiety (mean = 3.20), fear of negative evaluation (mean = 3.40), and fear of English class (mean = 3.02), demonstrated an average level of anxiety. Overall, FLA among the Islamic degree students was generally rated at a moderate level (mean = 3.28). Furthermore, the subsequent correlation analysis between FLA and students' exam grades displayed a weak positive relationship (r = 0.184), suggesting that FLA may offer facilitative insights into language learning performance.